Analysis of Investor Rights in Buying and Selling Shares Through Crowdfunding Services in Indonesia - Hakim, M. Rizky Aulia; Gunadi, Ariawan (Universitas Muhammadiyah Gorontalo, 2024)
This research highlights the significant role of POJK Number 57/POJK.04/2020 in establishing a legal framework for equity crowdfunding in Indonesia, aiming to balance investor protection and transaction flexibility. Despite its progress, challenges remain, particularly with restrictions on stock trading and limited investor flexibility. Equity crowdfunding services are rapidly growing in Indonesia as an alternative funding source for micro, small, and medium enterprises (MSMEs). However, the implementation of related regulations, particularly the Financial Services, faces challenges in protecting the rights of investors, especially regarding the restriction on share trading, which can only occur twice a year. This study aims to analyze the implementation of the POJK in accommodating investor rights and evaluate the role of platform providers in safeguarding investors' interests. Using a normative-empirical legal research method, the results show that although the regulation provides protection for investors, liquidity limitations and transparency of project reports remain significant challenges. The study concludes that increasing trading flexibility, technological development, and enhancing financial literacy are necessary to strengthen the equity crowdfunding ecosystem in Indonesia.